Planting The Seeds of Gratitude for Sustainable Corporate Social Responsibility and The Quality of Life - Ong Cordero, Ernesto (Future Science / FSH-PH Publications, 2023)
The study sought to determine the implementation of CSR activities and their effects on the beneficiaries' quality of life. This study used mixed-method research, combining quantitative correlational and qualitative analysis. In addition, it utilized statistical tools such as frequency, percentage, mean, weighted mean, and regression analysis. The research instrument was standardized and adopted from Kim, Uysal, and Sirgy's (2012) study entitled